2018
DOI: 10.1038/s41375-018-0218-6
|View full text |Cite
|
Sign up to set email alerts
|

European experience and risk factor analysis of donor cell-derived leukaemias/MDS following haematopoietic cell transplantation

Abstract: Donor cell leukaemia (DCL) is a rare complication of allogeneic haematopoietic cell transplantation (HCT). We have investigated the prevalence and outcome of donor cell haematology malignancies within centres registered with the European Society of Blood and Marrow transplantation (EBMT). We have sought to identify risk factors to shed light on the pathogenesis of DCL as a model for leukaemogenesis. DCL cases were identified by questionnaire and a follow-up questionnaire requested detailed data. Control subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
51
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(54 citation statements)
references
References 31 publications
1
51
1
1
Order By: Relevance
“…[14][15][16] DCL represents a relatively rare complication that affects 0.1% of those who undergo transplantion. 17,18 In addition, it has been shown that five of six recipients with unexplained cytopenias received allografts from donors with DNMT3A mutation. 19 Nonmalignant outcome consequences of donor CHIP, such as graft function and/or immunologic impairment, may be more common than DCL and may thereby contribute to HSCT outcome.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] DCL represents a relatively rare complication that affects 0.1% of those who undergo transplantion. 17,18 In addition, it has been shown that five of six recipients with unexplained cytopenias received allografts from donors with DNMT3A mutation. 19 Nonmalignant outcome consequences of donor CHIP, such as graft function and/or immunologic impairment, may be more common than DCL and may thereby contribute to HSCT outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of DCL has been estimated to range from less than 1 to 6.6% of all transplantations (2-10), and the frequency of DCL is increasing due to the increase in the number of SCTs (15). Dietz et al (9) reported that the risk of DCL was similar between stem cell sources.…”
Section: Discussionmentioning
confidence: 99%
“…Previous cases of DCL have been reported with all stem cell sources, including peripheral blood stem cells (2,9,10), bone marrow (2,9,11), and umbilical cord blood (5,9,(12)(13)(14). Umbilical cord blood is recognized as an alternative stem cell source for transplantation, and since 2005, some cases of DCL after cord blood transplantation (CBT) have been reported to have poor prognoses (12)(13)(14)(15).…”
Section: Introductionmentioning
confidence: 99%
“…Development of DCL especially after haploHSCT is a poorly reported phenomenon. Just recently, a multi-center survey of the European Society for Blood and Marrow Transplantation (EBMT) estimated a frequency of 80.5 DCLs per 100,000 alloHSCTs [3]. Since proof of DCL is generally difficult to obtain, the real prevalence is probably significantly higher.…”
Section: Dear Editormentioning
confidence: 99%